Coal-bearing strata of Labuan: Mode of occurrences, organic petrographic characteristics and stratigraphic associations - Abdullah, W.H.; Lee, C.P.; Gou, P.; Shuib, M.K.; Ng, T.F.; Albaghdady, A.A.; Mislan, M.F.; Mustapha, K.A. (Elsevier, 2013)
The current study describes the mode of occurrences of Labuan Cenozoic coals as observed in the field and identifies the coal macerals based on their organic petrographic characteristics as observed under reflected white light and blue light excitation. In this study some sedimentological aspects such as the depositional environment were correlated with the organic petrological characteristics of the coals. Based on the organic petrographic features and the thermal maturity as determined by vitrinite reflectance some new stratigraphic associations have been identified. Similarities in sedimentological and organic petrological characteristics suggest that the shaly strata associated with carbonaceous sandstones exposed on the north-western part of Labuan Island and the outcrop exposed in the south within the east Kiam Sam Peninsula belong to the same sequence within the Setap Shale Formation. Based on petrographic characteristics described and vitrinite reflectance values obtained from this study, at least four distinct units that are associated with coal-bearing sediments can be recognized. Strata with vitrinite reflectance (VR, %Ro) in the range of approximately 0.4–0.5% is the youngest and belongs to the Belait Formation which include the Tg. Layang-Layangan unit. The oldest sequence outcropping at Tg. Punei near the Labuan Crude Oil Terminal (Shell Terminal) belongs to the West Crocker Formation, possesses vitrinite reflectance in the range of 0.8–0.9%, whereas the intermediate unit is the Setap Shale Formation which possesses VR of 0.55–0.6% (including the East Kiam Sam sandstone unit) and Temburong Formation which possesses VR in the range of 0.65–0.75%.